Intervertebral disc degeneration—Current therapeutic options and challenges - Samanta, Ankita; Lufkin, Thomas; Kraus, Petra (Frontiers in Public Health, 2023)
Degeneration of the intervertebral disc (IVD) is a normal part of aging. Due to the spine's declining function and the development of pain, it may affect one's physical health, mental health, and socioeconomic status. Most of the intervertebral disc degeneration (IVDD) therapies today focus on the symptoms of low back pain rather than the underlying etiology or mechanical function of the disc. The deteriorated disc is typically not restored by conservative or surgical therapies that largely focus on correcting symptoms and structural abnormalities. To enhance the clinical outcome and the quality of life of a patient, several therapeutic modalities have been created. In this review, we discuss genetic and environmental causes of IVDD and describe promising modern endogenous and exogenous therapeutic approaches including their applicability and relevance to the degeneration process.